PUSAT KERAJINAN KRIYA DI BANJARBARU - Putri, Marina Elsyera Ika; Hartono, Rudi; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Various regions in Indonesia have various types of creative economic activities, one of which is the City of Banjarbaru. Banjarbaru has a leading economic sector, namely the craft sub-sector, which consists of embroidery sasirangan and woven purun. However, the development of the craft sector in Banjarbaru has not been matched by adequate facilities. The Handicraft Center in Banjarbaru is a public open space facility that is used to develop and introduce the potential of crafts, especially in the embroidery sasirangan and woven purun to the wider community. The Handicraft Center is designed with the aim of accommodating selected craft activities and attracting the interest of the general public through an approach to the built natural environment that is friendly to the users of the space as well as to the environment. To optimize the environmentally friendly context, the biophilic method is applied with the concept of natural nuances that are adapted to the activities, conditions and needs that exist at the craft center.